2022
DOI: 10.3892/mmr.2022.12694
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 exerts anti‑apoptotic effects on non‑alcoholic fatty liver cells by downregulating the expression of SGPL1

Abstract: Non-alcoholic fatty liver disease (NAFLD) has a high incidence, and can lead to liver cirrhosis and even hepatocellular carcinoma in severe cases. To the best of our knowledge, there is currently no safe and effective treatment for the management of this disease. Ginsenoside Rg1 (Rg1) is an active monomer derived from ginseng and notoginseng. In the present study, HHL-5 hepatocytes were used to establish an in vitro cell model of NAFLD by medium- and long-chain fat emulsion treatment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Ginsenoside Rg 1 competitively inhibits 2,3,7,8-tetrachlorodibenzodioxin (TCDD)-induced cytochrome P450 1A1 mRNA transcription by regulating aryl hydrocarbon receptor nuclear translocation, and it is a potent AhR agonist, so it can become a potentially effective drug for the prevention of TCDD-related liver injury [ 37 ]. Ginsenoside Rg 1 exerts an anti-apoptotic effect on nonalcoholic fatty liver cells [ 38 ]. Ginsenoside Rb 1 has a certain protective effect on liver toxicity induced by cantharidin in SD rats, which may be related to the up-regulation members of the MAPK family such as p -ERK, p -JNK and p -p38MAPK [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg 1 competitively inhibits 2,3,7,8-tetrachlorodibenzodioxin (TCDD)-induced cytochrome P450 1A1 mRNA transcription by regulating aryl hydrocarbon receptor nuclear translocation, and it is a potent AhR agonist, so it can become a potentially effective drug for the prevention of TCDD-related liver injury [ 37 ]. Ginsenoside Rg 1 exerts an anti-apoptotic effect on nonalcoholic fatty liver cells [ 38 ]. Ginsenoside Rb 1 has a certain protective effect on liver toxicity induced by cantharidin in SD rats, which may be related to the up-regulation members of the MAPK family such as p -ERK, p -JNK and p -p38MAPK [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the ameliorative role of Rg1 in NAFLD. Li et al demonstrated that Rg1 reduced fat accumulation in medium- and long-chain fat emulsion (MCE)-stimulated hepatocytes and protected the hepatocytes from NAFLD by inhibiting apoptosis via the suppression of the expression of sphingosine-1-phosphate lyase 1 (SGPL1), a key enzyme in the sphingosine signaling pathway [ 30 ]. Gu et al evaluated the effect of Rg1 on NAFLD by analyzing the serum proteins and transcriptome in rats.…”
Section: Pharmacological Roles Of Ginsengs and Ginsenosides In Nafldmentioning
confidence: 99%
“…Ginseng polypeptides consist of amino acids, which are precursor molecules of proteins that are easily absorbed by the body and have antibacterial, immune-enhancing, hypoglycemic, memory-improving, and hypoxia-resistant properties. They can also be used as a quality marker for different years of ginseng and have broad applications in the quality control of medicinal plants (Li G et al, 2022).…”
Section: Ginseng Polypeptidesmentioning
confidence: 99%